Tools for DNA adenine methyltransferase identification analysis of nuclear organization during C. elegans development. Issue 4 (21st April 2016) - Sharma, Rahul; Ritler, Dominic; Meister, Peter
Summary: C. elegans has recently emerged as a valuable model to understand the link between nuclear organization and cell fate, by combining microscopy approaches, genome‐wide mapping techniques with advanced genetics. Crucial to these analyses are techniques to determine the genome‐wide interaction pattern of proteins with DNA. Chromatin immunoprecipitation has proven valuable but it requires considerable amounts of starting material. This is sometimes difficult to achieve, in particular for specific genotypes (balanced strains, different sexes, severe phenotypes…). As an alternative to ChIP, DNA adenine methyltransferase identification by sequencing (DamID‐seq) was recently shown to be able to characterize binding sites in single mammalian cells. Additionally, DamID can be achieved for cell‐type specific analysis by expressing Dam fusion proteins under tissue specific promoters in a controlled manner. In this report, we present a user‐friendly pipeline to analyse DamID‐seq data in C. elegans . Based upon this pipeline, we provide a comparative analysis of libraries generated with different starting material and discuss important library features. Moreover, we introduce an adaptation of an imaging based tool to visualize in vivo the cell‐specific tridimensional binding pattern of any protein of interest. genesis 54:151–159, 2016. © 2016 Wiley Periodicals, Inc.